An Analysis of media representation of arab female athletes: the case of Al-Jazeera - Ajeel, Israa Hasan; Debbita Tan Ai Lin; Farhana Abdul Fatah (Penerbit Universiti Kebangsaan Malaysia, 2024)
The coverage of female athletes in sports media has been claimed to exhibit prejudice in favor of male athletes. Therefore, they promote the dominance of traditional masculine hegemony. Accordingly, the present study examines Al-Jazeera's coverage of Arab female athletes participating in the Rio Olympics. The study, therefore, aims to identify Al-Jazeera's strategies for covering Arab female athletes in selected online stories and their ideological perspectives in terms of "Self" or public and "Other" or private dichotomy. Furthermore, it aims to examine the feminist critical discourse analysis perspective in the gendered social practices of the Eastern world. This study analyses two Al-Jazeera news stories using feminist critical discourse analysis. Feminist critical discourse analysis challenges social practices related to gender stereotypes. Occasionally, gender inequalities are manifested explicitly as well as implicitly. Patriarchy persists in many social institutions and among women (and men) globally. The researchers implement Lazar's (2018) Feminist Critical Discourse Analysis. Thus, sports news ideological methods are analyzed using positive "in-group" and negative "out-group" dichotomy. The current research findings indicate that the patriarchal society has been transformed with respect to women's empowerment. Arab female athletes take place in public life as their male counterparts. However, the analyzed data demonstrated Arab women's gender resistance to the stereotypical gender norms. However, the current research is essential for revealing the progress of gender-based hierarchal social norms. Deconstructing conventional unequal gender roles is a key component of this research project's contribution to developing and promoting gender equality in Arabic culture.